The development and improvement of corn for the practical farmer of Kansas - Peterson, Jno. B. (My University, 1908)
Introduction: There are few agricultural plants that offer such advantages for improvement by breeding as the corn plant. The characteristics of the individual plant are of sufficient size to distinguish them readily; as, for example, the height of our ear on the stalk, the length of the shank, the size and shape of the ear, etc.
Citation: Peterson, Jno. B. The development and improvement of corn for the practical farmer of Kansas. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Kansas; Farming; Agriculture; Corn; Graduating theses; Senior theses; Theses